Hybrid MIMO-OFDM for Downlink Multi-User Communications Over Millimeter Channels with no Instantaneous Feedback - Lee, Po-Hsuan; Lin, Yuan-Pei (IEEE International Symposium on Circuits and Systems proceedings, 2019)
In this paper, we consider hybrid precoding for multiuser MIMO-OFDM systems in downlink communications with no instantaneous channel information. In a hybrid MIMO-OFDM, precoding consists of two parts: a RF (Radio Frequency) precoder that is subcarrier independent and subcarrier precoders that are subcarrier dependent. We design the precoders of both parts based on the statistics of the user channels, which requires infrequent feedback. To address interference among the users, the signals of different users are transmitted using spatially orthogonal beams. Due to the sparse nature of mmWave channels, the use of orthogonal beams leads to spatial separation among the users and effective prevention of interference. Simulations are given to show that the performance of the proposed statistical hybrid pre-coding system is close to that of a hybrid system that enjoys full-CSI (Channel State Information).